ANALISA GOOD CORPORATE GOVERNANCE (GCG) DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN: DATA PANEL - Fadli Halim; Hartaty Hadady; Fadli Ali Taslim (Jurnal Manajemen Sinergi, 2020)
Objective: This study aims to analyze the effect of GoodCorporate Governance (GCG) and Corporate SocialResponsibility (CSR) on the value of the company (Study of miningsector companies listed on the Indonesia Stock Exchange (IDX) in2013-2017). The sample selection in this study uses the PurposiveSampling method. Based on the results of the sample selection inaccordance with the criteria that have been made, it can beselected as many as 15 company samples or as many as 75 unitsof observation in a period of 5 years.Methodology: The analytical method used in this study is thePanel Data regression method with the Common Effect method.Finding: H1 are accepted, while H2 no accepted at the 5%confidence level.Conclusion: The results of this study indicate that Good CorporateGovernance (GCG) which proceeds with institutional ownershipnegatively affects company value. This can be seen from theprobability value of 0.009 which is smaller than the value of Î±(0.05), and the coefficient value of -0.57 indicates that there is anegative relationship between Good Corporate Governance (GCG)and the value of the company. while Corporate SocialResponsibility (CSR) does not affect the value of the company.This can be seen from the probability value of 0.529 which isgreater than the value of Î± (0.05), and the coefficient value of 0.081.